Challenges in Online Practical Learning Among Engineering Diploma Students: A Case Study at Kuching Polytechnic During the COVID-19 Pandemic - Ali, Amizanuryanti (Online Journal for TVET Practitioners, 2024)
The pandemic of COVID-19 has affected most of the education systems around the world and affected how schools conduct their daily activities. As a result, practical learning among polytechnic students has shifted to an online mode of delivery. This research investigated the challenges faced by engineering students when shifting the practical to online learning as well their stress level at Kuching Polytechnic Sarawak. The quantitative method was conducted with a sample size of 335 engineering students in Kuching Polytechnic, Sarawak. Challenges and stress levels experienced by students were gathered through an online survey using Google Forms. The findings of the study found that the device frequently used by students is a smartphone while the main method used by lecturers is to show videos from YouTube sources. The level of challenge and the level of student stress is moderate and there is no significant difference in the level of stress between genders. However, there is a significant relationship between the level of stress and the challenges faced by students during practical online learning. Overall, practical online learning caused challenges among students which also affects their stress levels. According to these findings, it is recommended that the Ministry of Higher Education should come up with a strategy by improving the infrastructure and provide TVET lecturers with specific training on using ICT in teaching practical in engineering education. Therefore, this issue needs to be thoroughly explored in order to prevent the delivery of practical online learning from becoming a barrier towards the students and lecturers in the future.